A serpin (CvT‐serpin15) of teratocytes contributes to microbial‐resistance in Plutella xylostella during Cotesia vestalis parasitism. Issue 10 (7th August 2021) - Gu, Qijuan; Wu, Zhiwei; Zhou, Yuenan; Wang, Zhizhi; Huang, Jianhua; Shi, Min; Chen, Xuexin
Abstract: BACKGROUND: Parasitic wasps are an important group of entomophagous insects for pest control. As parasitic wasps often lay eggs on or into their associated hosts, parasitoids evolve to utilize several factors including venom, polydnavirus (PDV) to alter host physiology for successful parasitism. Some taxa of endoparasitoids produce teratocytes, which are a type of cell that is released into host insects when wasp eggs hatch. Teratocytes display multifunction in parasitism such as host nutritional exploration, immune and developmental regulation, by secreting plenty of proteins into host hemocoel. RESULTS: A serpin (CvT‐serpin15) secreted by teratocytes was characterized. QPCR results showed the expressional level of CvT‐serpin15 was upregulated following bacterial challenges. Enzyme activity experiment indicated the recombinant CvT‐serpin15 protein could interfere with the growth of Gram‐positive bacteria Staphylococcus aureus . The survival rate assay demonstrated CvT‐serpin15 increased survival rate of Plutella xylostella infected by S. aureus . CONCLUSION: CvT ‐ serpin15 secreted by teratocytes would boost the host immune system when pathogens invade host hemocoel during parasitism, and ultimately protect the development of wasp larva from bacterial infection. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Teratocytes from endoparasitoid wasp secrete a CvT‐serpin15 protein, which inhibit the growth of bacteria and further contributes to microbial‐resistance of its host during parasitism. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.